Improving communication for persons with dementia - Mamo, Sara; Mayhew, Samantha J.; McNabney, Matthew; Oh, Esther S.; Lin, Frank R. (Canadian Acoustics, 2016)
Older adults with hearing loss and dementia may be particularly at risk for further cognitive and functional decline due to the combined effects of hearing loss and dementia on communication and social engagement. Further, the presence of hearing loss can exacerbate and magnify dementia symptoms, making the disease stage appear more severe than the person’s true cognitive function. Importantly, behaviors commonly assessed for guiding dementia care–including, depression, agitation, anxiety, apathy, and irritability–may be lessened by improved communication. The purpose of this project is to provide simple hearing intervention services in a group care environment to overcome some of the communication barriers as well as access to treatment issues faced by older adults with dementia and their families. By integrating services into an interdisciplinary, comprehensive health program, this project aims improve communication for at risk adults attending a Day Health Center for social engagement opportunities. Developing and implementing an affordable and accessible intervention that improves the listening environment, staff awareness, and use of amplification devices among individuals with dementia in group care settings provides a low-risk, low-cost, non-pharmacological treatment that may improve social engagement and reduce dementia-related behavioral symptoms.